Analysis of Pregnancy Outcomes Using the New IADPSG Recommendation Compared with the Carpenter and Coustan Criteria in an Area with a Low Prevalence of Gestational Diabetes. (10th January 2013) - Benhalima, Katrien; Hanssens, Myriam; Devlieger, Roland; Verhaeghe, Johan; Mathieu, Chantal
Abstract : Aims . This paper aims to evaluate characteristics and pregnancy outcomes in women prior classified normal by Carpenter and Coustan criteria (old criteria) and now gestational diabetes (GDM) by the IADPSG criteria. Methods . Retrospective analysis of 6727 pregnancies is used. Using the old criteria, 222 had GDM (old GDM). Using the IADPSG criteria, 382 had GDM of which 160 had a normal glucose tolerance with the old criteria (new GDM). We compared the new GDM group with the old GDM group and women with normal glucose tolerance with both criteria (NGT group, 6345). Results . New GDM women were younger (31.6 ± 4.7 versus 33.3 ± 7.2 years, P = 0.010 ) than old GDM women. Caesarean section was performed in 30.5% of new GDM, in 32.4% of old GDM (P = 0.706 ), and in 23.3% of NGT women (P = 0.001 ). Large for gestational age occurred in 10.8% of new GDM, in 13.8% of old GDM (P = 0.473 ), and in 9.0% of NGT women (P = 0.099 ). Shoulder dystocia occurred in 3.9% of new GDM, in 3.2% of old GDM (P = 0.736 ), and in 1.4% of NGT women (P = 0.007 ). Conclusion . Using the IADPSG criteria, more women are identified as having GDM, and these women carry an increased risk for adverse gestational outcome compared to women without GDM.